2016
DOI: 10.1016/j.jeurceramsoc.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the electric field-induced ferroelectric phase in Na0.5Bi0.5TiO3-KNbO3 ceramics

Abstract: Abstract(1-x)Na 0.5 Bi 0.5 TiO 3 -xKNbO 3 (NBT-xKN) ceramics, with x in the range 0.01 to 0.09, were prepared by solid state reaction and conventional sintering. A progressive transformation from a nano-polar to a long-range ordered ferroelectric phase was observed after the application of a cyclic electric field with an amplitude of 5 kV mm -1 . It is shown by analysis of the crushed ceramic pellets, using high resolution synchrotron x-ray diffraction, that the application the cyclic electric field induced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Further evidence can also be found from the appearance of the J‐E loops in that a single switching peak is observed at the FE coercive field. This type of irreversible electric field‐induced phase transformation was reported previously by Wang and Jo, who observed similar behavior in NBT‐KN and NBT‐BT solid solutions . In contrast, the constricted P‐E loops, for both NBT‐0.06NN and NBT‐0.08NN ceramics, are similar in appearance to those observed in other NBT‐based systems .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Further evidence can also be found from the appearance of the J‐E loops in that a single switching peak is observed at the FE coercive field. This type of irreversible electric field‐induced phase transformation was reported previously by Wang and Jo, who observed similar behavior in NBT‐KN and NBT‐BT solid solutions . In contrast, the constricted P‐E loops, for both NBT‐0.06NN and NBT‐0.08NN ceramics, are similar in appearance to those observed in other NBT‐based systems .…”
Section: Resultssupporting
confidence: 88%
“…To facilitate a comparison between the crystal structures of the NBT‐NN powders in the unpoled and poled states, the rhombohedral structure is transformed into the equivalent pseudo‐cubic setting following the method described previously . The results obtained for the changes in lattice parameter, a pc , and inter‐axial angle, α pc , as a function of composition for the NBT‐xNN solid solution system are illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were made for the other NBT‐KN compositions investigated in this study and therefore the patterns were fitted using the R 3 c space group in order to obtain the refined lattice parameters in the hexagonal setting of the rhombohedral structure. The resulting crystallographic parameters were transformed into the equivalent pseudo‐cubic setting, using the method described previously …”
Section: Resultsmentioning
confidence: 99%
“…In a recent publication, it was observed using high‐energy synchrotron XRD that NBT‐ x KN ceramics with x =0.02‐0.08 displayed a pseudo‐cubic structure in the unpoled state but also exhibited well‐formed polarization‐field (P‐E) hysteresis loops for low KN contents, indicating the presence of an electric field‐induced FE phase . Subsequently, it was confirmed that a structural transformation from pseudo‐cubic to rhombohedral had occurred under the influence of an alternating electric field …”
Section: Introductionmentioning
confidence: 96%